2021
DOI: 10.3390/foods10112649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Non-Pruning on Main Quality Constituents in ‘Dancong’ Tea (Camellia sinensis) Leaves Based on Proteomics and Metabolomics Analysis

Abstract: ‘Dancong’ tea is a famous traditional Oolong tea. In order to keep the original taste of “ancient tea trees”, most of the ‘Dancong’ tea plants are planted in a single plant pattern without pruning. The objective of this study was to explore the effects of long-term non-pruning on main quality constituents in ‘Dancong’ tea. The results showed that the contents of free amino acids, chlorophylls, and floral-honey aromatic substances in tea leaves of unpruned tea plants were higher than those in every year pruned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…These metabolites were grouped into 11 classes, and major metabolites included flavonoids (146), phenolic acids (65) and lipids (67). These were followed by amino acids and derivatives (33), nucleotides and derivatives (31), organic acids (31), alkaloids (18), lignans and coumarins Differentially changed metabolites in P1 (A) and P2 (B). (14), tannins (10), and terpenoids (2).…”
Section: The Differences In Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…These metabolites were grouped into 11 classes, and major metabolites included flavonoids (146), phenolic acids (65) and lipids (67). These were followed by amino acids and derivatives (33), nucleotides and derivatives (31), organic acids (31), alkaloids (18), lignans and coumarins Differentially changed metabolites in P1 (A) and P2 (B). (14), tannins (10), and terpenoids (2).…”
Section: The Differences In Metabolitesmentioning
confidence: 99%
“…(14), tannins (10), and terpenoids (2). They were further grouped into 30 sub-classes, including flavonols (34), free fatty acids (28), saccharides and alcohols (20), flavanols (18), flavonoid carbonoside (17), Lysophosphatidylcholine (15), proanthocyanidins (14), anthocyanins (9), and isoflavones (4).…”
Section: The Differences In Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Sun et al (2018) identified impacts of longterm tea plant pruning on catechins through metabolomic and transcriptomic techniques, with epigallocatechin gallate (EGCG) and caffeine notably lower in leaves of unpruned tea plants relative to leaves of pruned plants, which leads to less astringency and bitterness of the commercial tea produced from unpruned plants. Chen et al (2021) used the sensory evaluation panels to find that tea leaves from unpruned plants had the best aroma and taste, and biochemical assays yielded complementary results in which the amino acid and aromatic compound contents were significantly higher in leaves of unpruned tea plants than in leaves of pruned tea plants. These differences in amino acids, aromatic compounds and secondary metabolites may be a primary reason why tea from unpruned tea plants is generally considered the most fresh and mellow.…”
Section: Pruning Affects the Accumulation And Proportions Of Tea Leaf...mentioning
confidence: 99%
“…Some arbor-type tea plants are grown without pruning in order to maintain the original tea taste. Chen et al (2021) explored Dancong tea quality and found that total amino acid content and chlorophyll content of tea leaves increased significantly when pruning was withheld, while the content of catechins decreased significantly. In the same study, the concentrations of aromatic compounds with floral and honey aromas were also significantly higher in tea not subjected to pruning, with notable examples including methyl salicylate, benzyl alcohol, benzeneacetaldehyde, jasmine lactone and trans-nerolidol (Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%